Lipid Dynamics in Membranes Slowed Down by Transmembrane Proteins - Ebersberger, Lisa; Schindler, Torben; Kirsch, Sonja A.; Pluhackova, Kristyna; Schambony, Alexandra; Seydel, Tilo; Böckmann, Rainer A.; Unruh, Tobias (Frontiers in Cell and Developmental Biology, 2020)
Lipids and proteins, as essential components of biological cell membranes, exhibit a significant degree of freedom for different kinds of motions including lateral long-range mobility. Due to their interactions, they not only preserve the cellular membrane but also contribute to many important cellular functions as e.g. signal transport or molecular exchange of the cell with its surrounding. Many of these processes take place on a short time (up to some nanoseconds) and length scale (up to some nanometers) which is perfectly accessible by quasielastic neutron scattering (QENS) experiments and molecular dynamics (MD) simulations. In order to probe the influence of a transmembrane sequence of the transferrin receptor (TFRC) protein on the dynamics of 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) large unil- amellar vesicles (LUVs) on a nanosecond time scale, high-resolution QENS experiments and complementary MD simulations have been utilized. By using different scattering contrasts in the experiment (chain-deuterated lipids and protonated lipids, respectively), a model could be developed which allows to examine the lipid and protein dynamics separately. The experimental results revealed a restricted lipid lateral mobility in the presence of the TFRC transmembrane proteins. Also the apparent self-diffusion coefficient of the lateral movement of the protein molecules could be determined quantitatively for the probed short-time regime. The findings could be confirmed very precisely by MD simulations. Furthermore, the article presents an estimation for the radius of influence of the proteins on the lipid long-range dynamics which could be determined by consistently combining results from experiment and simulation.